Construction purchasing & supply chain management - Benton, W. C. Jr.; McHenry, Linda F. (New York, 2010)
Monstruction Purchasing & Supply Chain Management is an authori-C tative guide that provides proven strategies for the construction supply chain management (CSCM) function. The material in this book explains how to achieve maximum integration with upstream and downstream supply chain members using the latest methodolo-gies and technologies. It is also a comprehensive step-by-step guide to CSCM that is intended to help project owners, design engineers, archi-tects, prime contractors, subcontractors, suppliers, and construction managers involved in construction projects throughout the world establish a strategic framework to meet the budgetary and scheduling goals of any project. This book can be used to teach the fundamentals of construction purchasing and supply management in a logical, sim-ple, and concise format in construction management courses designed for undergraduate business and civil engineering students or for con-struction management graduate students. CSCM focuses on strategies for Lean construction including just-in-time purchasing, supplier eval-uation, subcontractor selection, subcontractor relationship manage-ment, equipment acquisition, information sharing, and project qual-ity management. The treatment of CSCM in this book is extensive and complete. There are more than 70 illustrations and ready-to-use forms.
Keywords: Building materials - purchasing